EFFECT OF MONITORING AND EVALUATION IMPLEMENTATION ON THE PERFORMANCE OF UNIVERSAL SECONDARY EDUCATION SCHOOLS IN KINYAMASEKE TOWN COUNCIL, KASESE DISTRICT. A CROSS-SECTIONAL STUDY. - MASEREKA , SULAIT; Sendagi , Mohammed (Student's Journal of Health Research Africa, 2024)
Background: The study investigated the effect of Monitoring and Evaluation implementation on the performance of Universal Secondary Education schools in Kinyamaseke Town Council, Kasese District Methodology: The study employed a descriptive research design and the main data collection instruments were questionnaires and interviews. The study findings were aimed at answering the study objectives whose details have been presented concerning 64 respondents. SPSS (Statistical Package for Social Scientists) was used as well. Results: The majority of the respondents were male 67% (43) as compared to female respondents33% (21) and most of them were within the age group 45% (31-50). Findings revealed a significant moderate positive correlation (rho= .495) between M&E implementation and performance of USE schools whereby better M&E implementation was related to better performance of USE schools and poor M&E implementation was related to poor performance of USE schools. M&E implementation accounted for a 24.5% variance in the performance of USE schools. Both M&E information gathering and M&E accountability had a significant effect on the performance of USE schools. However, M&E information gathering had a greater effect on the performance of USE schools compared to that of M&E accountability. Conclusion: The study demonstrates the importance of M&E implementation in the performance of schools. The positive relationship between M&E implementation in organizational performance emphasizes that school activities should be performed well for the schools to run well. Recommendation: Ministry of Education and Sports should put in place a mechanism to keep stakeholders informed of USE M&E activities, periodically publish its USE M&E annual financial report, and have clear informative USE M&E reports.